2023
DOI: 10.1177/21676968231151776
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Self-Control and Distress Among Emerging Adults: A Serial Mediating Roles of Fear of Missing Out and Social Media Addiction

Abstract: Previous studies have confirmed that poor self-control, fear of missing out (FoMO), and social media addiction are potential risk factors for young mental health. However, the relationships between self-control, FoMO, social media addiction, and emerging adult distress have received relatively little attention in empirical studies. In this regard, drawing on the self-determination theory (SDT), the current study investigates the serial mediating roles of FoMO and social media addictions between self-control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 106 publications
1
1
0
Order By: Relevance
“…Our results also indicate that FoMO and ON-FoMO are strongly positively correlated with depression and SMA, thus confirming previous research findings [ 22 , 23 , 25 , 63 , 64 , 65 ]. These data can be interpreted in light of self-determination theory (SDT) [ 13 , 14 ], according to which psychological needs such as autonomy, competence, and relationship can account for motivations for using social media, especially among adolescents and young adults.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also indicate that FoMO and ON-FoMO are strongly positively correlated with depression and SMA, thus confirming previous research findings [ 22 , 23 , 25 , 63 , 64 , 65 ]. These data can be interpreted in light of self-determination theory (SDT) [ 13 , 14 ], according to which psychological needs such as autonomy, competence, and relationship can account for motivations for using social media, especially among adolescents and young adults.…”
Section: Discussionsupporting
confidence: 92%
“…Undoubtedly one of the most remarkable and useful adaptations to the human psyche is the ability to exercise self‐control (Tangney et al, 2004). Previous research has shown that while high self‐control is related to greater academic success, better adaptation, positive health habits, and better interpersonal relationships (Duckworth & Seligman, 2005; Şimşir & Dilmaç, 2022; Tangney et al, 2004), low self‐control is associated with addictions, poor mental health, lower school performance, and procrastination (Bertrams & Dickhäuser, 2009; Koç et al, 2023; Şimşir Gökalp et al, 2022). For these reasons, the ability to self‐control is a desired characteristic; therefore, it is crucial to investigate the factors increasing and decreasing self‐control.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ego strength model has been extensively investigated in the laboratory setting (e.g., Baumeister et al, 1998), cross‐sectional studies are relatively scarce in the literature. Most of these cross‐sectional studies were performed with adult participants (e.g., Koç et al, 2023; Nielsen et al, 2020). To the best of our knowledge, no study has been performed to investigate the connections between procrastination, stress, and self‐control employing a mediator model among adolescents in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…FoMO is a phenomenon commonly described as a persistent sense of anxiety or worry that other people have enjoyable experiences without their participation and is often marked by a strong need to stay updated on others' activities [ 42 ]. Lack of self-control is a risk factor for mental health, and social media addiction and fear of missing out (FoMO) further raise this risk [ 43 ]. For example, users of WeChat, Messenger, and WhatsApp, which are primarily messaging apps, demonstrate distinct behavioral patterns compared with those of image-based social networking platforms such as Instagram.…”
Section: Introductionmentioning
confidence: 99%